THE INTEGRATION OF ETHICS AND CLINICAL REASONING IN AVICENNA’S CANON OF MEDICINE - Umrullayeva Jasmina Gayrat qizi, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: Avicenna (Ibn Sina) is one of the most influential physicians in the history of medicine, whose work The Canon of Medicine established a comprehensive system combining clinical reasoning with medical ethics. This article explores how Avicenna integrated ethical principles with diagnostic and therapeutic reasoning. His approach emphasized patient-centered care, accurate diagnosis, professional responsibility, and moral conduct in clinical decision-making. The relevance of these principles to modern evidence-based medicine and medical ethics is also discussed.